1995
DOI: 10.3109/00365549509032747
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Quinolones for Successful Eradication of Multiply Resistant Vibrio Cholerae in Adult Patients

Abstract: There has been an increasing multiple drug resistance problem in Vibrio cholerae biotype Eltor, the causative agent of 7th pandemic. The aim of this study was to show in vitro and in vivo susceptibility and effectiveness of quinolones in the treatment of endemic cholera cases. Excellent results were obtained in 53 bacteriologically confirmed cholera patients treated with short-term ofloxacin and ciprofloxacin. To our knowledge, there has been no previous report on this subject in the international medical lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Changes in susceptibility pattern have been attributed to isolation time, source and geographical location. However, high activities of ofloxacin and ciprofloxacin observed in our study are similar to other studies [15, 38, 39] and corroborate the use of fluoroquinolones as new alternatives for cholera treatment in some cholera endemic regions [40]. Our data and reports from other cholera endemic localities in Douala [20] therefore suggest ciprofloxacin and ofloxacin could be very good alternatives for chemotherapy during cholera or cholera-like disease outbreaks in Douala.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in susceptibility pattern have been attributed to isolation time, source and geographical location. However, high activities of ofloxacin and ciprofloxacin observed in our study are similar to other studies [15, 38, 39] and corroborate the use of fluoroquinolones as new alternatives for cholera treatment in some cholera endemic regions [40]. Our data and reports from other cholera endemic localities in Douala [20] therefore suggest ciprofloxacin and ofloxacin could be very good alternatives for chemotherapy during cholera or cholera-like disease outbreaks in Douala.…”
Section: Discussionsupporting
confidence: 92%
“…Almost all O1 and non-O1 strains displayed susceptibility to the broad-spectrum fluoroquinolones, such as ciprofloxacin and ofloxacin. It is important to note, however, that two clinical O1 strains showed intermediate resistance to these drugs while clinical studies have shown that these drugs are effective in the treatment of cholera [31,32], the emergence of fluoroquinolone-resistant strains of V. cholerae O1 has been reported [28]. The results from this study suggest that the treatment of diarrhoeal patients with alternative drugs such as fluoroquinolones will probably become problematic in the future due to the emergence of resistance.…”
Section: Analysis Of Antibiotic Resistancementioning
confidence: 74%
“…The antibiotics that were effective with all the studied strains were ciprofloxacin and doxycycline, which connected with other antibiotics as the fluoroquinolones are being evaluated nowadays to determine new alternatives in the treatment against the cholera but whose use is uncommon in our country [29][30][31]. In developed countries, these antibiotics would be probably the election drugs because they quickly reduce the fecal excretion of Vibrio, and they can cover a wide spectrum of enteropathogens including V. cholera.…”
Section: Discussionmentioning
confidence: 99%